2018
DOI: 10.1038/s41598-018-29496-2
|View full text |Cite
|
Sign up to set email alerts
|

Subtle left-right asymmetry of gene expression profiles in embryonic and foetal human brains

Abstract: Left-right laterality is an important aspect of human –and in fact all vertebrate– brain organization for which the genetic basis is poorly understood. Using RNA sequencing data we contrasted gene expression in left- and right-sided samples from several structures of the anterior central nervous systems of post mortem human embryos and foetuses. While few individual genes stood out as significantly lateralized, most structures showed evidence of laterality of their overall transcriptomic profiles. These left-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 95 publications
7
57
0
Order By: Relevance
“…Assuming that hand dominance and/or division of labour between the hands is beneficial for fine motor control, then the fact that we have two hands essentially imposes a binary choice on a developmental program which may be more continuous in its original nature. The fact that human brain embryonic gene expression has been shown to be only very subtly lateralized is consistent with such a model (45,46).…”
Section: General Observationssupporting
confidence: 63%
“…Assuming that hand dominance and/or division of labour between the hands is beneficial for fine motor control, then the fact that we have two hands essentially imposes a binary choice on a developmental program which may be more continuous in its original nature. The fact that human brain embryonic gene expression has been shown to be only very subtly lateralized is consistent with such a model (45,46).…”
Section: General Observationssupporting
confidence: 63%
“…Reproducibility across samples and emerging cross-study consensus also in early development suggests a genetic influence upon cortical thickness asymmetry 58 , and genetic factors have recently been implicated in the dynamics of age-related cortical change across life 36 . One can speculate whether age-related asymmetry breakdown is a by-product of genetic factors encoding the asymmetric organization of cortex 60 supporting hemispheric specialization of function, and that this differentiation leads to downstream neural consequences in aging. Though anatomo-functional relationships are likely complex 61 , our results suggest that cortical thickness asymmetry may constitute a viable anatomical marker for key aspects of human hemispheric specialization.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression and in utero ultrasound studies of human embryos have indicated that lateralized development is already underway in the human central nervous system by 5 to 8 weeks postconception, [6][7][8] which indicates a genetic-developmental program underlying the typical form of functional brain laterality. One study reported a nonsignificant heritability (<1%) for the laterality of speech sound perception, based on the dichotic listening method, and considering the full range of trait variation from left-to right-ear-advantage.…”
mentioning
confidence: 99%